Corporate investment and cash flow sensitivity: what drives the relationship? - Paul Mizen; Philip Vermeulen (European Central Bank (ECB), 2005)
The excess sensitivity of investment to cash flow has been demonstrated in numerous studies. Recent research has identified differences in the degree of sensitivity across countries, which it ascribes to the nature of the lender-borrower relationship in the financial systems of those countries. In this paper we offer new methods and results to determine whether differences are associated with structural explanations such as the nature of the financial system and industrial composition, or due to other firm-specific determinants such as size or creditworthiness. Unlike previous research we are able to systematically control for competing explanations in our data from more than one country and thereby isolate what drives the relationship. We find that creditworthiness is the main driving force of cash flow sensitivity.
Keywords: E22; D92; 330; cash flow sensitivity; corporate investment; cross-country investment studies; Investition; Cash Flow; Sensitivitätsanalyse; Großbritannien; Deutschland